Skholé : um modo de vida - Gandolfi, Neura Maria (My University, 2016)
A lifestyle with skholé seems to have been experienced in Classical Greece, in the beginning of the philosophy birth between the X and VII centuries B. C. and improves between the VI and IV centuries B.C. Aristotle is beyond question the one who gives you a more systematic treatment and a greater relevance to confer prestige when it postulates the onset of philosophy and science as a result of free time. Aristotle in his books, The Politics and the Nicomachean Ethics, uses structural concepts to demonstrate what types of life and how they interfere with the formation of character, the deliberation process and the achievement of the action. Understand the work as necessary to supply human needs and consumption, open debate on the free time to the contemplative life. The expository analysis goes around of the concept of skholé with the purpose to try to indicate the place on the contemporary philosophical-ethical debate, even in the context of applied ethics. Contemporary man needs to rescue a type of occupation that is not business, nor obligation, but skholé, entertainment and leisure as essential not only for the physical and mental health but also for the constitution of the moral character and an ethics and happy human existence.
Um modo de vida com skholé parece ter sido vivenciado na Grécia Clássica, nos primórdios do nascimento da filosofia, entre os séculos X e VII a. C., e se aperfeiçoa entre os séculos VI e IV a. C. Aristóteles é sem dúvida quem lhe dá um tratamento mais sistemático e uma relevância mais notável ao conferir-lhe prestígio quando postula o surgimento da filosofia e da ciência como resultado do tempo livre. Nas obras A Política e a Ética a Nicômaco, ele utiliza conceitos estruturantes para demonstrar quais os tipos de vida e como eles interferem na formação do caráter, no processo de deliberação e na realização da ação. Compreender o trabalho como necessário para suprir as necessidades humanas e o consumo, abre o debate sobre o tempo livre para a vida contemplativa. A análise expositiva gira em torno do conceito de skholé com o objetivo de tentar indicar o seu lugar no debate éticofilosófico contemporâneo, inclusive no âmbito das éticas aplicadas. O homem contemporâneo precisa resgatar um tipo de ocupação que não seja negócio, nem obrigação, mas skholé, ócio ou lazer, como imprescindível não só para a saúde física e mental, mas também para a constituição do caráter moral e para uma existência humana ética e feliz.
Keywords: Estilo de vida; Lazer; Filosofia; Lifestyles; Leisure; Philosophy